The Application of Diffusers for Classroom Acoustical Design. (May 2014) - Choi, Young-Ji
This study investigates the application of periodic type diffusers for improving the acoustics in classrooms and proposes an optimum combination of absorptive and diffusing treatments for achieving preferred acoustics in classrooms. The measurements were carried out in a 1/10 scale model classroom, adding different amounts of absorptive and diffusing materials to one or more of five surfaces of the room. Adding combinations of diffusers and absorptive materials to the surfaces of the classroom achieved higher early-to-late arriving sound ratio (C50) corresponding to higher clarity. Diffusers were beneficial for enhancing the early arriving reflection energy (G50) at the most distant seats and they resulted in achieving more uniform acoustical conditions across the room. The treatment of the front wall with diffusers was found to lead to better acoustical conditions than treating the rear and side walls with diffusers. Adding diffusers on the ceiling and lower front wall or side wall and adding diffusers on the ceiling and absorptive materials on the lower front wall were selected for consideration as the more successful treatments for classroom acoustical design.